Efeitos do alopurinol na proteção renal por meio da dosagem plasmática e urinária de biomarcadores e histologia: estudo em modelo experimental de lesão de isquemia e reperfusão em ratos sob anestesia inalatória - Bussmann, André Roberto [UNESP] (2014)
Ischemic and reperfusion kidney injury are involved in many clinical conditions. The reperfusion injury leads to reactive oxygen species formation and allopurinol has the potential to inhibit this process. The novel biomarkers can perform early diagnosis of acute kidney injury. The purpose of this study was to investigate whether allopurinol had a renal protective effect measuring renal function, novel biomarkers levels (pNGAL, uNGAL and IL-18) and studying histopathologic features during renal ischemia–reperfusion (I/R) injury in uninephrectomized rats. 32 Wistar Rats were randomized in 4 groups: Sham (S): laparotomy and right nefrectomy. Control (C): laparotomy and right nefrectomy, I/R maneuvers in left kidney. Allopurinol Control (AC): laparotomy and right nefrectomy, pretreated with allopurinol 100mg.kg-1.d-1. Allopurinol (A): laparotomy and right nefrectomy, I/R maneuvers in left kidney, pretreated with allopurinol 100mg.kg-1.d-1. pNGAL, uNGAL, IL-18, KIM-1, serum creatinine and histopathologic features were analysed. Differences in the mean values were deemed significant at P<0.05. All groups showed a significant rise in serum creatinine throughout the experiment being A≈C>S≈AC. pNGAL and IL-18 showed a significant rise in all groups too, however all of them evolve in a similar way. uNGAL showed signifcantly rise in group C, but all of them evolve in a similar way. KIM-1 was higher in group A than C and had intermediate values in groups S and AC. With regard to histopathologic features, C and A groups showed left kidney injury signifcantly higher than S and AC groups. There were no difference in histopathologic features between groups C and A neither between S and AC. Allopurinol given 100mg.kg-1.d-1 did not seem to exert protective or harmful effects in kidneys that underwent I/R injury under functional, novel biomarkers levels and histopathologic features evaluation